2013
DOI: 10.1902/cap.2012.110085
|View full text |Cite
|
Sign up to set email alerts
|

Orthodontic Treatment After Induced Periodontal Regeneration in Deep Infrabony Defects

Abstract: Introduction: Limited studies investigated whether orthodontic movement should be performed in patients with periodontal disease and severe intrabony defects. The purpose of this study is to assess the stability of the periodontal complex combining regeneration treatment with enamel matrix derivative (EMD) and collagen bovine mineral bone, followed by early orthodontic movement. Case Series: In a prospective case series, 10 patients with radiographic vertical defects with probing depths (PDs) ≥6 mm and patholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(48 citation statements)
references
References 28 publications
3
40
0
Order By: Relevance
“…Case series/reports have documented improvement of intrabony defects with orthodontic tooth movement alone, including bodily movement into intrabony defects; 169,172,173 extrusive movement, such as a mesially tilted tooth with 1‐ or 2‐wall intrabony defect; 168,170,171 and orthodontic intrusion 174‐176 . Moreover, case reports suggest no adverse effects of orthodontic movement of teeth that had previously undergone regenerative therapy for intrabony defects 178‐180 …”
Section: The Relationship Of Regenerative Treatment To Endodontic Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Case series/reports have documented improvement of intrabony defects with orthodontic tooth movement alone, including bodily movement into intrabony defects; 169,172,173 extrusive movement, such as a mesially tilted tooth with 1‐ or 2‐wall intrabony defect; 168,170,171 and orthodontic intrusion 174‐176 . Moreover, case reports suggest no adverse effects of orthodontic movement of teeth that had previously undergone regenerative therapy for intrabony defects 178‐180 …”
Section: The Relationship Of Regenerative Treatment To Endodontic Andmentioning
confidence: 98%
“…[174][175][176] Moreover, case reports suggest no adverse effects of orthodontic movement of teeth that had previously undergone regenerative therapy for intrabony defects. [178][179][180] Recently, the first RCT evaluated the role of combined periodontal regenerative orthodontic treatment of 2-or 3-wall intrabony defects. 177 In this clinical trial, 47 patients were randomized into orthodontic extrusive force with pretreatment grafting of EMD + DFDBA plus orthodontic extrusion (test group) or EMD + DFDBA grafting alone (control group).…”
Section: The Relationship Of Regenerative Treatment To Endodontic Andmentioning
confidence: 99%
“…Indeed, several longer-term case series and reports with a follow-up of at least 3 years after regenerative surgery have shown favourable outcomes with such a delayed approach (Ghezzi et al 2008;Jepsen et al 2015;Roccuzzo et al 2018;Aimetti et al 2020). In contrast, other reports have suggested that orthodontic therapy may be initiated much earlier (either immediately up to 3 months after the regenerative procedure) (Cardaropoli et al 2001;Cardaropoli et al 2006;Ogihara & Wang, 2010;Attia et al, 2012;Ghezzi et al 2013;Attia et al 2019). The authors reported no adverse effects and speculated that early tooth movement could even stimulate periodontal wound healing.…”
mentioning
confidence: 99%
“…Clinical studies examining the effect of orthodontic treatment on patients with infrabony defects are limited and report different results [ 21 , 22 ]. A case report on teeth with infrabony pockets and pathologic migration showed that orthodontic movement did not have a negative effect on newly regenerated periodontal tissues [ 23 ]. Another study showed that orthodontic movement could increase the destruction severity of the connective tissue attachment on teeth with inflamed, infrabony defects [ 24 ].…”
Section: Discussionmentioning
confidence: 99%